Reconstructing patterns of vegetation recovery and landscape evolution after a catastrophic landslide (Mont Granier, French Alps, 1248 CE). (December 2022) - Quiquerez, A.; Gauthier, E.; Bichet, V.; Petit, C.; Murgia, L.; Richard, H.
Abstract: Investigating past human-environment interactions provides clues to understand landscape responses to catastrophic events. This study uses a multiproxy approach to reconstruct landscape change over the past 800 years, in an area where slopes and soils were reshaped by the Mont Granier landslide (French Alps) in 1248 CE. Pollen and sediment analyses of an 89-cm sediment core retrieved from Lake St. André, a lake formed by the landslide, were used to reconstruct vegetation recovery and agro-pastoral activities. These analyses of lake sediments were supplemented by studying land-cover changes based on cadastral maps. Aerial photographs provided information about spatial landscape organization from the 18th century onwards. Results showed that significant changes in land-use systems were closely linked to social, political, and economic events. Rapid recolonization by pioneer vegetation communities began just after the landslide. Despite short phases of conflict-induced agricultural decline, agro-pastoral activities diversified from the 16th century onwards, with land use dominated by croplands, vineyards, and grasslands. The extension of arable lands, particularly vineyards, continued until the 19th century. At the beginning of the 20th century, this territory was characterized by an agro-pastoral economy based on mixed family farming. From the 1960 s onwards, cattle grazing ceased, and dairy production was replaced by viticulture. Changes in the agro-pastoral system after the landslide therefore reflect complex geomorphological, political, social, and economic interactions. This study also demonstrates how a multiproxy approach can decipher landscape evolution and reveal the human-environment interactions behind landscape change.